Concepts of good mental health and wellbeing in people with intellectual disability: Study protocol for a systematic review - Komenda, Sophie; Brunevskaya, Nadine; Moritz, Paula; Landskron, Sarah Jasmin; Zrnic Novakovic, Irina; Oberleiter, Sandra; Wurzer, Jana; Lueger-Schuster, Brigitte; Salvador-Carulla, Luis; Zeilinger, Elisabeth L. (Frontiers in Psychiatry, 2023)
Introduction: Good mental health is an indispensable aspect of good general health and different definitions of good mental health have been developed for the general population. However, it is not clear how these definitions can be applied to people with intellectual disabilities (ID), as they may have difficulties in many facets encompassed in existing definitions. Yet, people with ID can be mentally healthy or mentally ill just as people without ID. Objective: The aim of this systematic review is to summarize existing concepts, definitions, and measurement approaches of good mental health and wellbeing for people with ID. Methods: A comprehensive, systematic literature review will be conducted in eleven databases, including ASSIA, CINAHL, Cochrane Library, ERIC, MedRxiv, OSF preprints, ProQuest Dissertations & Theses Global, PsycINFO, PubMed, Scopus, and Web of Science. By including preprints and theses servers in the search strategy, we will also consider grey and unpublished literature. The quality of included studies will be rated using standardized checklists. All steps of the literature search, data extraction, and quality rating will be performed independently by two trained researchers. Disagreements will be resolved through discussion between these researchers and, if required, by consulting a third team member. In a narrative synthesis, existing approaches to good mental health and wellbeing for people with ID will be systematically described and linked to current research in mental health for people with and without ID. Discussion: The findings of this study will provide researchers and practitioners with an evidence-based overview of current approaches to good mental health and wellbeing of people with ID. We will explore and discuss the individual facets of the definitions, concepts, and measurement approaches and identify possible gaps which need to be addressed. This will strengthen future research on this topic and focus research activities on important and unresolved themes that need to be targeted to promote health equity for people with ID.